(untitled) (Baghdad Science Journal, 2025)
Blood samples were collected from (31) pregnant women infected with cytomegalovirus , also (15) blood samples were collected from congenitally infected infants, and (20),(15),(15) blood samples were collected from pregnant women ,non pregnant and infants, respectively, all of them were as control groups. CMV infection identified by using ELISA assay to detect specific CMV IgM & IgG in sera. The results of lymphocyte transformation showed a significant decrease when phytoheamagglutinin (PHA) used as stimulator, lymphocytes response in infected pregnant women was lower than that of non infected pregnant women as well as non pregnant women. Result also showed a significant decrease in the ability of lymphocyte division in healthy pregnant women when compared with healthy non pregnant women. Lymphocyte activity of infants infected with CMV was also significally lower when comparison with non infected infants.